2021
DOI: 10.3390/ijerph18126403
|View full text |Cite
|
Sign up to set email alerts
|

Self-Rated Health and Psychological Distress among Emerging Adults in Italy: A Comparison between Data on University Students, Young Workers and Working Students Collected through the 2005 and 2013 National Health Surveys

Abstract: Background. The present study aimed at comparing self-reported physical health and mental health among university students, workers, and working students aged between 19 years and 29 years. Method. Using data from National Health Surveys held in 2005 and 2013, a cross-sectional study was conducted on 18,612 Italian emerging adults grouped into three groups: university students, workers, and working students. The odds ratios of self-reported anxiety or depression, poor general health, and poor mental health and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 83 publications
0
13
0
1
Order By: Relevance
“…Appendix A shows the survey questions relating to physical activity in all domains for the 1999–2000 and 2004–2005 surveys, in English and Italian. These physical activity measures are not externally validated, but have been used in several national surveys and in different epidemiological studies (d’Errico et al 2019 ; Franzoi et al 2021 ; Gandini et al 2019 ; Piccinelli et al 2018 ). For OPA, in both surveys, employed participants were asked: ‘Is your work mostly characterised by physical activity?’.…”
Section: Methodsmentioning
confidence: 99%
“…Appendix A shows the survey questions relating to physical activity in all domains for the 1999–2000 and 2004–2005 surveys, in English and Italian. These physical activity measures are not externally validated, but have been used in several national surveys and in different epidemiological studies (d’Errico et al 2019 ; Franzoi et al 2021 ; Gandini et al 2019 ; Piccinelli et al 2018 ). For OPA, in both surveys, employed participants were asked: ‘Is your work mostly characterised by physical activity?’.…”
Section: Methodsmentioning
confidence: 99%
“…Mental health is affected by complex reasons, such as socio-demographic characteristics [13], lifestyles [14], occupational status [15], as well as self-rated health [16] and social networks [17,18]. Social support quality (SSQ) is considered as another critical influencing factor for mental health status [19], and dissatisfaction with insufficient or poor-quality social supports is closely associated with mental health problems [20].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, there is a strong need for clinical psychology and psychotherapeutic interventions. Indeed, psychotherapeutic work can promote transformations that, in addition to increasing quality of life, can help students evolve toward healthier ways of relating on both the individual and interpersonal levels [15,148]. Nonetheless, only a few studies have focused on psychotherapy, and, most notably, long-term interventions [63,64,149].…”
Section: Discussionmentioning
confidence: 99%
“…Frequently, this transitional period takes place during the years of higher education, which implies further tasks and demands [7][8][9]. Several studies [10][11][12][13][14] have shown that university students report higher levels of anxiety and depression, as well as lower levels of perceived health, and are at greater risk for poor mental health than, for example, their working peers [15] and the general population [16,17]. Thus, it is of fundamental importance to design and provide comprehensive psychological interventions to support emerging adults through this complex transition, with a specific focus on those in higher education [18][19][20].…”
Section: Introductionmentioning
confidence: 99%